The effect of gastrointestinal nematode infection level on grazing distance from dung - Sarti Seo, Hizumi Lua; Pinheiro Machado Filho, Luiz Carlos; Honorato, Luciana Aparecida; Da Silva, Bruna Fernanda; Talamini do Amarante, Alessandro Fernando [UNESP]; Bricarello, Patrizia Ana (Public Library Science, 2015)
Avoiding grazing near feces is an efficient strategy to prevent parasitic infection and contamination; therefore, in the evolution of herbivorous species, this behavior may have developed as a mechanism to protect the host against infection by gastrointestinal nematodes. The aim of this study was to assess whether grazing distance from dung is related to the level of parasitic infection in cattle. Based on Fecal Egg Count (FEC) means, 18 castrated male steers, aged 18 months, were divided into three groups: High (FEC >= 315); Medium (FEC = 130-160); and Low (FEC = 40-70). To analyze the response to a new natural infection by gastrointestinal nematodes and to standardize infection levels, all animals received anthelmintic treatment at twenty days prior to field observation. Three observers simultaneously collected data on grazing behavior for 2.5 hours/week for 12 weeks. Observers recorded the distance when grazing occurred at less than one meter from dung. Every two weeks, fecal samples were collected for FEC, as well as serum samples to measure immunoglobulin G (IgG) levels against larvae and adult antigens of the parasitic species Haemonchus placei. All groups grazed farther from the dung on days of greater insolation (r = 0.62; P = 0.03). Animals with high levels of parasitism grazed farther from the dung (P < 0.05) but had lower levels (P < 0.0001) of IgG serum levels compared to those with medium and low levels of infection. FEC values varied over the experiment, remaining below 200 for the low and medium group and reaching 1000 (P < 0.01) for the animals with the highest rates of parasitism. Our results indicate that cattle showing high levels of parasitism are more likely to avoid contaminated areas than animals with lower infection levels, and the immune system seems to be involved in such behavior.